Penerapan Metode Composite Performance Index (CPI) Dalam Penerima Bantuan Kelompok Usaha Bersama (KUBE) - Zainab Sipahutar; Berto Nadeak; Putri Ramadhani (Universitas Budi Darma, 2021)
A joint business group is a group of citizens or a group of social communities formed from families classified as poor communities through a social welfare program, abbreviated as prokesos, which is useful for carrying out business to increase the income of a group of underprivileged residents. In the decision-making process, errors and inaccuracies in the distribution of aid to the community, for example, people who do not deserve assistance but who receive assistance are inversely proportional to poor communities who do not receive assistance. This problem arises because of the lack of careful selection and miscalculation in determining which people are entitled to receive assistance. For this reason, it is necessary to have a decision support system in producing decisions so that it can support the decisions made by the Province of Social Affairs more real. In this study, one of the Composite Performance Index (CPI) methods is used which is expected to be able to assist the Provincial Social Service in determining the appropriate kube in receiving assistance.